Pengaruh Employee Engagement dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Karawang - Muhamad Jaka Umbaran; Suroso Suroso; Dwi Epty Hidayaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of employee engagement and work discipline on employee performance at the Karawang Regency Population and Family Planning Control Office (DPPKB), both partially and simultaneously. The research method used was a quantitative survey approach. The study population consisted of 38 DPPKB employees in Karawang Regency, all of whom served as the research sample. Data collection was conducted through questionnaires, while data analysis used validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that employee engagement had a positive and significant effect on employee performance with a significance value of 0.004 (<0.05). Work discipline also had a positive and significant effect on employee performance with a significance value of <0.001 and was the variable with the most dominant influence. Simultaneously, employee engagement and work discipline had a positive and significant effect on employee performance with a calculated F-value of 108.708 and a significance level of <0.001. The coefficient of determination (R²) of 0.861 indicates that 86.1% of the variation in employee performance can be explained by employee engagement and work discipline, while the remaining 13.9% is influenced by other factors outside the study. The conclusion of this study is that employee engagement and work discipline are important factors that significantly influence employee performance at the Karawang Regency DPPKB, with work discipline being the variable with the greatest influence on employee performance improvement. Keywords: Employee Engagement, Work Discipline, Employee Performance, Civil Servant